Blast loaded plates: Simplified analytical nonlinear dynamic approach. (December 2020) - Mohammadzadeh, Behzad; Kang, Junsuk; Im, Seokbeen
Graphical abstract: Abstract: In this study, a novel simplified nonlinear dynamic method was presented to investigate the blast loaded plates. The material nonlinearity, strain rate, and various boundary conditions were included in the method together with plate geometry, scaled distance, and charge weight. The novelty of this work is that this method is easy-to-use while it covers all the important parameters affecting the blast-related dynamic responses of the isotropic plates. Equations of motion were achieved by applying the Navier solution to the dynamic governing equation of the plate. To include the material nonlinearity, the Ramberg-Osgood model, and hardening behavior were adopted. For the strain rate, the Cowper-Symonds relation was considered. Two types of boundary conditions were considered; simply supported and clamped plates. The scaled distance and charge weigh were included in the description of the blast load while the plate geometry was shown up in the stiffness and frequency of the plate. The method was validated by comparing the time history and maximum deflection of the plates obtained from the proposed method and those of the literature and finite element model through ABAQUS. Thereafter, a parametric study was carried out to examine the effects of plate aspect ratio, thickness, charge weight, and boundary conditions on the dynamic responses of the steel plates. The results showed that the plate deflection had a nonlinear relation with plate thickness, aspect ratio, and explosive charge while the clamped boundary condition resulted in a significant decrease in the maximum plate deflection.